A STUDY ON ADOPTION OF INFORMATION TECHNOLOGY IN SMALL ENTERPRISES - Khaund, Manoj; Nath, Bimal Deb (IJRDO - Journal of Business Management, 2022)
The Small businesses are considered the backbone of industrial development. They represent the economic development model and act as the engine of growth for the same, focusing on high contribution to domestic production, significant export revenues and influential contribution to foreign exchange. Small enterprises have to compete and survive with large enterprises, which is currently one of their biggest problems. One of the reasons for this disadvantage is that small enterprises lack information technology advantages. Mostly, these enterprises fail to use information technology in business operations, severely limiting their performance and survival. Businesses must have the adequate IT infrastructure to give them a competitive advantage. This leads to a mechanism that provides the right information at the right time and place. As the use of IT accelerates in business, rapid implementation of IT enabled services in small businesses is required. Information systems are important applications of information technology in business management. However, there are still problems in the implementation of IT by these small enterprises. This paper attempts to highlight the main factors and advantages in implementing and adopting information technology in small enterprises.